VIRTUAL SPACE OF COLLEGE LIBRARY - Kudriavtseva, Olga (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article discusses the representation of college libraries in the Internet. The author insists on discarding outdated professional paradigms and on developing new models of library-user relationship.